Answer:
1/21
Step-by-step explanation:
2/7 ÷ 6 =
2/7 x 1/6 = 2/42
Simplify by dividing the numerator and denominator by 2
1/21
If my answer is incorrect, pls correct me!
If you like my answer and explanation, mark me as brainliest!
-Chetan K
Answer:
-57
Step-by-step explanation:
<h2><u>Use BOMAS</u></h2>
B- brackets
O- of
M- multiplication
A- addition
S - subtraction
-3[1+2(4+5)]
first solve what is in the brackets
(4+5) = 9
place 9 in the brackets
-3[1+2(9)]
now multiply the 2 and 9
2*9 = 18
-3[1+18)]
1+ 18 = 19
now multiply the (-3) with 19
= <u>-57</u>
To get the answer you would:
Multiply 525 by 1.2 525*1.2=
which equals 630
then you would add 525 to 630 525+630=
So the answer would be:
1155
Hope this helps
(6^-2)^2 = 1/1296 = 0.0007716049382716 hope this is what you were looking for. the math is right tho for (6^-2)^2 most calculators can do this easy just do 6^-2 then after just do ^2
=(-4/5)^2 * -3/50
square -4/5 first; remember -4/5^2 is the same as -4/5 * -4/5
=(-4/5 * -4/5) * -3/50
multiply -4 numerators; multiply 5 denominators
=(-4 * -4)/(5 * 5) * -3/50
=16/25 * -3/50
multiply numerators 16 & -3; multiply denominators 25 & 50
=(16 * -3)/(25 * 50)
= -48/1250
simplify by 2
= -24/625 (or -0.0384)
ANSWER: -24/625 (or -0.0384)
Hope this helps! :)